A skin-inspired soft material with directional mechanosensation. (10th June 2021) - Makhoul-Mansour, Michelle M; Challita, Elio J; Chaurasia, Adarsh; Leo, Donald J; Sukharev, Sergei; Freeman, Eric C
Abstract: Lessons about artificial sensor design may be taken from evolutionarily perfected physiological systems. Mechanosensory cells in human skin are exquisitely sensitive to gentle touch and enable us to distinguish objects of different stiffnesses and textures. These cells are embedded in soft epidermal layers of gel-like consistency. Reproducing these mechanosensing capabilities in new soft materials may lead to the development of adaptive mechanosensors which will further enhance the abilities of engineered membrane-based structures with bioinspired sensing strategies. This strategy is explored here using droplet interface bilayers embedded within a thermoreversible organogel. The interface between two lipid-coated aqueous inclusions contained within a soft polymeric matrix forms a lipid bilayer resembling the lipid matrix of cell membranes. These interfaces are functionalized with bacterial mechanosensitive channels (V23T MscL) which convert membrane tension into changes in membrane conductance, mimicking mechanosensitive channel activation in mammalian mechanosensory cells. The distortion of encapsulated adhered droplets by cyclical external forces are first explored using a finite element composite model illustrating the directional propagation of mechanical disturbances imposed by a piston. The model predicts that the orientation of the droplet pair forming the membrane relative to the direction of the compression plays a role in the membrane response. The directional dependence of mechanosensitive channel activation in response to gel compression is confirmed experimentally and shows that purely compressive perturbations normal to the interface invoke different channel activities as compared to shearing displacement along a plane of the membrane. The developed system containing specially positioned pairs of droplets functionalized with bacterial mechanosensitive channels and embedded in a gel creates a skin-inspired soft material with a directional response to mechanical perturbation.